eggNOG 4.5: a hierarchical orthology framework with improved functional annotations for eukaryotic, prokaryotic and viral sequences - Huerta-Cepas, Jaime; Sunagawa, Shinichi; Bork, Peer (Nucleic acids research, 2016)
Abstract. eggNOG is a public resource that provides Orthologous Groups (OGs) of proteins at different taxonomic levels, each with integrated and summarized fun